EXPERIENCE IN APPLYING THE TECHNOLOGY OF CYTOREDUCTIVE SURGERY WITH HYPERTHERMIC INTRAOPERATIVE INTRAPERITONEAL CHEMOTHERAPY IN THE TREATMENT OF PATIENTS WITH PERITONEAL CARCINOMATOSIS - A. V. Shelekhov; V. V. Dvornichenko; S. I. Radostev; D. D. Morikov; R. I. Rasulov; I. V. Ushakova; A. A. Medvednikov; A. G. Zaharov; R. N. Demonov; O. V. Gladkova; N. M. Chernorubashkina (Сибирский онкологический журнал)
We present our experience in using cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) for ovarian cancer patients treated at Irkutsk Regional Cancer Center. All patients were divided into 2 groups. Group I  consisted of 15 patients, who underwent cytoreductive surgery only.  Group II comprised 17 patients, who underwent surgery and HIPEC.  The main eligibility criteria for this study were verified peritoneal carcinomatosis and resectable ovarian cancer. The primary analysis of these groups included: preoperative period, length of  operation, postoperative length of stay, and postoperative  complications. The technique of performing HIPEC using Performer  HT® (RAND, Medolla (MO), Italy) was completely described. Further study is required to estimate the difference in overall and disease-free survival between study groups.